Formulation Design and Development of Fast Disintegrating Tablets of Losartan Potassium By Using Locast Bean Gum As Superdisintigrants - Singh, Kehar; Dadabhau, Gaikwad Dushyant; Singh, Satbir (International Journal of Membrane Science and Technology, 2023)
For patients who have trouble swallowing tablets, capsules, etc., fast dissolving drug delivery devices provide an option. Water is not necessary for the swallowing of fast dissolving pills because they dissolve instantly in the mouth. Using locust bean gum as a natural superdisintegrant, the present work set out to produce fast-dissolving tablets of losartan potassium. Perform pre formulation studies like partition coefficient, solubility and identification of drug. The influence of precompressional parameters like interaction studies and compatibility. Other tablet properties were examined, as well as the impact of formulation parameters on losartan potassium disintegration and in-vitro dissolution. The findings indicated that the 7.5% concentration of locust bean gum had good superdisintegrant qualities and produced quickly dissolving tablets. The best tablet formulation (F3) had a 20-second minimum disintegration time and a 30-minute maximum drug release of 98%. The locust bean gum was discovered to have a notable ability to be employed as a superdisintegrant, with a swelling index of 22. The DSC analysis and IR spectra demonstrated that there was no interaction of any type with the tablet's formulation ingredients. Accelerated short-term experiments on optimized formulation show no appreciable modifications to the formulation.